The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/14647273.2017.1358828
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to modern, widespread environmental endocrine disrupting chemicals and their effect on the reproductive potential of women: an overview of current epidemiological evidence

Abstract: Growing evidence indicates that exposure to widespread, environmental contaminants called endocrine disruptors (EDCs) negatively affects animal and human reproductive health and has been linked to several diseases including infertility. This review aims to evaluate the impact of environmental exposure to endocrine disrupting chemicals [phthalates, parabens, triclosan, bisphenol A (BPA), organochlorine (PCBs) and perfluorinated (PFCs) compounds] on the reproductive potential among women, by reviewing most recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 84 publications
0
68
0
2
Order By: Relevance
“…In addition, prenatal exposure to BP causes impaired neurodevelopment . Moreover, as urinary BP increases with the progress of pregnancy, it is presumed that the metabolism of BP is also influenced by physiological alteration during pregnancy . It is also known that BP is closely related to the metabolism of endocrine disruptors such as BPA, which is known to adversely affect placental development .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, prenatal exposure to BP causes impaired neurodevelopment . Moreover, as urinary BP increases with the progress of pregnancy, it is presumed that the metabolism of BP is also influenced by physiological alteration during pregnancy . It is also known that BP is closely related to the metabolism of endocrine disruptors such as BPA, which is known to adversely affect placental development .…”
Section: Discussionmentioning
confidence: 99%
“…As BP is widely contained in various beauty products, women of childbearing age are easily exposed to it, but the risk is not reported due to its relatively low content and toxicity. However, a recent study of BP‐induced histopathological or proteomic changes in the female reproductive organs of animal models suggested that the accumulation of BP may affect offspring . Based on this study, it is necessary to identify the adverse effects of BP, which accumulates in the placenta during pregnancy, and to study its stability.…”
Section: Discussionmentioning
confidence: 99%
“…octylphenol and nonylphenol), BPA shows xenoestrogen exhibiting estrogen-mimicking properties ( Nimrod & Benson, 1996 ). Numerous studies have demonstrated adverse health effects attributed to BPA including a range of reproductive problems such are reduced fertility, male and female reproductive tract abnormalities, metabolic disorder, cancer induction, neurotoxicity and immunotoxicity ( Richter et al, 2007 ; Manfo et al, 2014 ; Karwacka et al, 2017 ; Giulivo et al, 2016 ; Ho et al, 2006 ; Itoh et al, 2012 ; Kimber, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, bisphenol-A(BPA) is a member of alkylphenol family and is used primarily to make plastics, and products using BPA-based plastics have been available in commercial since 1957 ( Nimrod & Benson, 1996 ; Pivnenko et al, 2015 ). More recently, BPA is a preferred color developer in carbonless copy paper and thermal point of sale receipt paper ( Karwacka et al, 2017 ). Actually, BPA seems to be most commonly exposed industrial EDC in modern society, and its adverse effects have been extensively studied over past two decades ( Giulivo et al, 2016 ; McLachlan, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental exposure is known to interfere with reproduction (fertility disorders, pregnancy pathologies, and developmental abnormalities) [1,2]. Exposure to certain chemical or physical agents (solvents, heavy metals, pesticides, drugs, ionizing radiation, heat) is associated with alterations of spermatic parameters [3][4][5], negative effects on fertility in women [6], spontaneous abortions, and congenital malformations [7,8], as well as certain adverse pregnancy outcomes (fetal death, intrauterine growth retardation (IUGR), and prematurity) [7]. In addition, environmental exposure during fetal life may increase the risk of chronic disease in childhood and adulthood (hypothesis of the developmental origins of health and disease (DOHaD)) [9].…”
Section: Introductionmentioning
confidence: 99%